Evaluating the use of a customized digital navigation program to optimize bowel preparation in pediatric colonsocopy - Dankner, Lauren; Quiros, Jose Antonio; Volpert, Diana; Atreja, Ashish (Frontiers in Pediatrics, 2023)
Introduction Adequate bowel preparation is essential for optimal colonoscopy diagnosis and/or intervention. However, suboptimal bowel preparation occurs in as many as 1 in 3 pediatric colonoscopies, leading to missed diagnoses, procedural complications, wasted resources, and increased costs. We aimed to evaluate the effect of an automated Pediatric Colonoscopy Digital Navigation Program (PC-DNP) on the quality of colonoscopy preparation among pediatric patients. Methods The PC-DNP sent patients timely weight-based bowel preparation instructions, video and text-based educational modules, logistical information, and appointment reminders prior to their scheduled diagnostic and/or therapeutic colonoscopies. Physician reported bowel preparation quality among patients/caregivers who were prescribed the PC-DNP were compared to bowel preparation quality of a historical sample of patients/caregivers who received standard care instructions. Results We found that the PC-DNP group had significantly higher bowel preparation quality than the standard care group. Conclusions These results demonstrated that automated DNPs may be easily implemented into the pediatric gastroenterologists' practice and may help streamline and improve bowel preparation in pediatric patients.